Targeting Phosphodiesterases—Towards a Tailor-Made Approach in Multiple Sclerosis Treatment - Schepers, Melissa; Tiane, Assia; Paes, Dean; Sanchez, Selien; Rombaut, Ben; Piccart, Elisabeth; Rutten, Bart P. F.; Brône, Bert; Hellings, Niels; Prickaerts, Jos; Vanmierlo, Tim (Frontiers in Immunology, 2019)
Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system (CNS) characterized by heterogeneous clinical symptoms including gradual muscle weakness, fatigue, and cognitive impairment. The disease course of MS can be classified into a relapsing-remitting (RR) phase defined by periods of neurological disabilities, and a progressive phase where neurological decline is persistent. Pathologically, MS is defined by a destructive immunological and neuro-degenerative interplay. Current treatments largely target the inflammatory processes and slow disease progression at best. Therefore, there is an urgent need to develop next-generation therapeutic strategies that target both neuroinflammatory and –degenerative processes. It has been shown that elevating second messengers (cAMP and cGMP) is important for controlling inflammatory damage and inducing CNS repair. Phosphodiesterases (PDEs) have been studied extensively in a wide range of disorders as they breakdown these second messengers, rendering them crucial regulators. In this review, we provide an overview of the role of PDE inhibition in limiting pathological inflammation and stimulating regenerative processes in MS.